Cross-cultural analysis of the stigmatising attitudes of psychiatrists across Europe and measurement invariance of the Opening Minds Stigma Scale for healthcare providers. (1st June 2022) - Ori, D.; Szocsics, P.; Molnar, T.; Rozsa, S.; Wallies, M.; Kazakova, O.; Bankovska-Motlova, L.; Boivin, S.; Raaj, S.; Overgaard Ingeholm Klinkby, I.M.; Cabacos, C.; Pereira, A.T.; et al.
Abstract : Introduction: Since the literature investigating the stigmatising attitudes of psychiatrists is scarce, this is the first study which examines the phenomena across Europe. The Opening Minds Stigma Scale for Health Care Providers (OMS-HC) is a widely used questionnaire to measure stigma in healthcare providers towards people with mental illness, although it has not been validated in many European countries. Objectives: A cross-sectional, observational, multi-centre study was conducted in 32 European countries to investigate the attitudes towards patients among specialists and trainees in general adult and child psychiatry. In order to be able to compare stigma scores across cultures, we aimed to calculate measurement invariance. Methods: An internet-based, anonymous survey was distributed in the participating countries, which was completed by n=4245 psychiatrists. The factor structure of the scale was investigated by using separate confirmatory factor analyses for each country. The cross-cultural validation was based on multigroup confirmatory factor analyses. Results: When country data were analysed separately, the three dimensions of the OMS-HC were confirmed, and the bifactor model showed the best model fit. However, in some countries, a few items were found to be weak. The attitudes towards patients seemed favourable since stigma scores were less than half of the reachable maximum. Results allowed comparison to be made between stigma scores in different countries and subgroups. Conclusions: This international cooperation has led to the cross-cultural validation of the OMS-HC on a large sample of practicing psychiatrists. The results will be useful in the evaluation of future anti-stigma interventions and will contribute to the knowledge of stigma. Disclosure: No significant relationships.